Socio-economic drivers of increasing number of slums in Chile - Vergara Perucich, José Francisco. (Sciendo, 2022)
Between 2017 and 2020 the number of households living in slums in Chile has increased by 73.52%, which has led the state to urgently develop housing solutions to reorient public policy in this area. This article contributes to this discussion through an exploratory statistical analysis to identify the socio-economic drivers that best help to explain the formation of slums in Chilean cities. The resulting predictive model is tested in Greater Santiago, the nation's capital, with good results, validating its usefulness for the design of housing policies. Among the results, low household income and the presence of international immigrants explain an increase in the probability of housing precariousness, while the presence of renters and heads of household with postgraduate degrees decreases this possibility. In addition to the specific scope for the Chilean case, the article shares a methodological strategy that can be replicated in other countries and cities to develop similar diagnoses. Highlights for public administration, management and planning: A predictive model is developed using census data to identify the areas of the city where vulnerability of housing measured by socioeconomic factors may reflect precariousness of housing. Areas of the city with high rate of international immigrants and/or low-income households tend to predict precariousness of housing. Areas of the city where households' heads have postgraduate degrees and/or are tenants tend to have less probability of developing precarious housing.
Keywords: LISA; ocioeconomic determinants; Alojamiento; Barrios bajos